Assessing the Impact of Textual Content Concreteness on Helpfulness in Online Travel Reviews. (April 2019) - Shin, Seunghun; Chung, Namho; Xiang, Zheng; Koo, Chulmo
The online travel review has become one of the most influential information sources for travelers' decision making. This research primarily aims to examine the relationship between review textual content concreteness and review helpfulness in the tourism context. In particular, we examine how this relationship plays out under two individual circumstances, namely, temporal distance and risk–benefit tendency. Based on the construal level theory and feeling-as-information theory, two experiments are conducted to test whether the influence of review concreteness is moderated by temporal distance and risk–benefit tendency. The results show that the main effect of review concreteness is significant; however, in contrast to the assumptions of theories and results of relevant studies, both interaction effects of temporal distance and risk–benefit tendency are not. Finally, we interpret the findings and discuss the implications and limitations of this research.